RANCANG BANGUN KOMBINASI ALAT-MESIN ROLLER-CHOPER UNTUK PENYIAPAN BAHAN PAKAN HIJAUAN PADA RUMINANSIA - , NURHADI SAPUTRO, S.Pd; , Prof. Dr. Ir. Ali Agus, DAA., DEA. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
With an area of agricultural land to reach 53.71 million ha, and 6.4 million ha of plantations in the country gives us enough reason to encourage the rapid advancement of the livestock sector, especially livestock cultivation. Blitar district has land area of 32,578 % km 2 , 30.74% of agricultural land, forest 21.56 %, 16.19% residential, and plantations 8.48 %, there maining water and other. To support the mechanization of forage processing of agricultural waste and plantation is absolutely Necessary engineering roller machine-chopper. This machine expected to result in crushing and cutting of soft, shorten time of enumeration, and reduce operasioning cost preparing food. The proses of rolling and cutting machine that do this is to forage. Prototype manufacturing equipment ô± machine made by a conventional engine and local part. Recently engine chopper is one chopper without combination rollers, also has not been able to cut with small demensions for cattle food. So the combination of machine tool designed to position two length wise groove roller spring pressure and equipped units that can be set and replaced according to the size of the processed forage or hardness material to be rolled and cut. Chopper blade consists of 4 pieces, with a draining spoon to remove of the result. This research attempts to offer a solution to this problem by designing wake combination of tools - roller machine-chopper is driven by a Diesel engine with a power of 8 HP, working capacity-average 500 kg/hour with fuel consumption of 500 ml/hour.The use of a combination of tools-these machines can reduce the cost of feed processing can be reduced to 19.7% in the appeal of feed processing manually.